Carrier concentration-dependent piezotronic and piezo-phototronic effects in ZnO thin-film transistor. (July 2018) - Pan, Zijian; Peng, Wenbo; Li, Fangpei; He, Yongning
Abstract: The piezotronic and piezo-phototronic effects have been confirmed as promising methodologies to optimize the performances of electronic/optoelectronic devices. Here, the carrier concentration dependence of both the piezotronic and piezo-phototronic effects are systematically investigated in ZnO thin-film transistors (TFTs) that fabricated by high-concentration solution hydrothermal method (ZnO NW TFT) and radio frequency magnetron sputtering (ZnO seed TFT) method. Significant performance improvement is achieved in the ZnO NW TFT with moderate carrier concentration by the piezotronic effect, whereas the photoresponse performance of the ZnO NW TFT to 365 nm UV illumination shows no modulation by the piezo-phototronic effect. In contrast, the performance of the ZnO seed TFT with ultra-low carrier concentration almost keeps unchanged when introducing the piezotronic effect, while significant photoresponse improvement of the ZnO seed TFT to 365 nm UV illumination is obtained by the piezo-phototronic effect. After careful analysis and comparation, the different influences of piezotronic and piezo-phototronic effects in the ZnO NW TFT and the ZnO seed TFT are resulted from the different carrier concentrations in ZnO NW film and ZnO seed film with or without UV illumination. This study not only presents in-depth understanding about carrier concentration dependence of the piezotronic and piezo-phototronic effects in ZnO TFTs, but also provides feasible, compatible and adjustable methodologies to enhance/optimize the performances of electronic/optoelectronic devices. Graphical abstract: fx1 Highlights: The first time to systematically investigate both the piezotronic and piezo-phototronic effects in ZnO TFTs. Significant performance improvement is obtained in ZnO TFTs by the piezotronic and piezo-phototronic effects. The piezotronic and piezo-phototronic effects in ZnO TFTs are strongly dependent on the carrier concentration.